Effect of spray droplet size on herbicide efficacy on four winter annual grasses. (October 2018) - Ferguson, J. Connor; Chechetto, Rodolfo G.; Adkins, Steve W.; Hewitt, Andrew J.; Chauhan, Bhagirath S.; Kruger, Greg R.; O'Donnell, Chris C.
Abstract: In Australia, winter annual grasses provide the strongest competition against wheat for resources which detrimentally affects grain yield. With increasing action from government, industry, and grower groups to reduce herbicide spray drift, adoption of drift reduction technologies (DRTs) especially DRT nozzles has increased over recent years. Some herbicides are less effective when sprays are too coarse as droplets may not be retained on target weed surfaces or not intercepted by target leaves. This is particularly an issue with winter annual grasses, whose small, narrow leaves and ability to grow within the wheat canopy makes their control more difficult. This study sought to understand the effect of droplet size on herbicide efficacy by evaluating the effect of six nozzles, five of which have DRT features across six different herbicides (amitrole, clodinafop, glyphosate, imazamox plus imazapyr, metribuzin, and paraquat) for the control of four winter annual grasses (annual ryegrass, Italian ryegrass, rescuegrass, and tame oats). Plants were grown in pots outdoors on the University of Queensland Gatton campus and were sprayed at 28 days after emergence in August and repeated in October 2015. Results from this study indicate DRT nozzles that produce sprays classified as Ultra-Coarse (>650 μm Dv0.5 ) can preserve efficacy for some herbicides. Differences were not observed for herbicide efficacy of clodinafop, imazamox plus imazapyr, and glyphosate across both years. Coarse sprays appear to provide the most herbicide efficacy across a wide array of modes of action, and yet reduce spray drift potential compared to finer sprays. Highlights: Spray droplet size did not affect herbicide efficacy for systemic herbicides. Amitrole and paraquat efficacy were reduced with the TTI nozzle. Coarse sprays resulted in similar herbicide efficacy for Fine or Medium sprays. Clodinafop was not an effective control option for rescuegrass. Ultra Coarse sprays controlled winter annual grasses similar to Fine sprays.